Regionalism, Productivity, and Innovation - Rolando Avendano; Massimiliano Tani; Lovely C. Tolin (Institute of Labor Economics (IZA), 2024)
In this paper, we examine whether, and if so how, an economy's deliberate policy choices of regional cooperation and integration influence underlying determinants of economic growth. Building on models of growth and innovation, we analyze the role of regional integration on labor productivity and firms' probability to innovate using data from a panel of 170 economies and 60,000 firms over a period of two decades. Our results suggest that regionalism, as captured by metrics of regional cooperation and integration, can positively contribute to labor productivity and innovation, in addition to known factors of production.
Keywords: F02; F15; O4; O30; 330; regional integration; productivity; innovation; Asia